DOI: 10.11606/t.5.2016.tde-20052016-142644
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades auditivas e de linguagem de crianças usuárias de implante coclear: análise dos marcadores clínicos de desenvolvimento

Abstract: LISTA DE GRÁFICOS Gráfico 1 Desempenho da amostra na IT-MAIS durante, no mínimo, 60 meses de uso do IC (N=230) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
21

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 111 publications
(203 reference statements)
2
15
0
21
Order By: Relevance
“…In this research, it was observed that, after nine months of CI use, all the children presented detection skills; after five years of CI use, three of them attained maximum auditory skills (comprehension), providing correct answers for more than 50% of the listened words. A relevant study described the existence of a gradual pattern in the development of the auditory skills of children using CIs; after nine months, the children are expected to be capable of detecting sounds and to start identifying words, and after five years, they are expected to recognize words in an open set, i.e., they are capable of recognizing and extracting a word's phonemic information only by listening to it, having, therefore, developed the listening comprehension skill [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, it was observed that, after nine months of CI use, all the children presented detection skills; after five years of CI use, three of them attained maximum auditory skills (comprehension), providing correct answers for more than 50% of the listened words. A relevant study described the existence of a gradual pattern in the development of the auditory skills of children using CIs; after nine months, the children are expected to be capable of detecting sounds and to start identifying words, and after five years, they are expected to recognize words in an open set, i.e., they are capable of recognizing and extracting a word's phonemic information only by listening to it, having, therefore, developed the listening comprehension skill [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the development of auditory and oral language skills in the population of children using CIs can be close to the language profile of normal-hearing children whose chronological age is equal to the time of CI use and that it is expected that, after five years of use of the device, the children will have reached the maximum auditory and language performance [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estas últimas Categorias (4 e 6) foram atingidas pelas crianças após 37 e 25 meses de uso do IC, respectivamente, mas é importante registrar que a criança que atingiu a Categoria de Audição "6" obteve uma piora nesta avaliação no último retorno e os motivos serão discutidos posteriormente. Comerlatto (2016) verificou-se que 1,7% das crianças estavam na Categoria de Audição "2", 3% na categoria "3", 8,6% na categoria "4", 24,3% na categoria "5" e 62% na categoria "6". Já no atual estudo, embora tenha sido observada a tendência de uma curva crescente ao longo dos cinco anos de uso, o crescimento se mostrou discreto, com grande diferença nas categorias atingidas com decorrer do tempo de uso: 21,1% das crianças se encontravam na Categoria de Audição "1", 55,7% das crianças na categoria "2" e 21,1% na categoria "3" e uma das crianças não estava utilizando o dispositivo.…”
Section: Caracterização Do Desenvolvimento Auditivounclassified
“…As crianças do presente estudo atingiram a Categoria de Audição "2" com um a quatro meses de uso e a categoria "3" somente foi alcançada por seis crianças a partir dos 13 meses de uso. Em comparação com os resultados obtidos por Comerlatto (2016), em média, as crianças passaram a atingir a Categoria de Audição "2" com cinco a oito meses de uso do IC e a Categoria de Audição "3" com nove meses de uso, sendo os resultados deste estudo inferiores ao encontrado pela autora. Considera que cabe ao médico otorrinolaringologista assistente a indicação de necessidade de troca ou manutenção do processador de fala do sistema de implante coclear.…”
Section: Caracterização Do Desenvolvimento Auditivounclassified
See 1 more Smart Citation